Tamil movies and Singaporean South Indian teenagers. - Sathiavathi Chinniah. (2010)
The purpose of this study was to examine the relation between Tamil movies and Singaporean South Indian teenagers. Much of the inspiration for this research was obtained from two previous studies. One was conducted by Blumer, in the early 1930s, under the Payne Fund studies to explore the effects of motion pictures on teenagers. The other research, carried out by Sara Dickey, in the early 1990s, studied Indians in Madurai (a South Indian State) and their reactions to Tamil movies. Apart from these studies, a general concern of Tamil movies being a negative influence on local South Indian teens and the fact that no formal academic research has been carried out in this area, despite this concern, also served as a great impetus in encouraging the author to carry out research in this topic. Data for this research was collected from 70 students aged between 15 and 18. These students were from six secondary schools which were selected on a stratified random basis. They were told to write autobiographical accounts on what they have learnt from Tamil movies. In addition, conversations were also held with participants to find out more about their views on this issue. Apart from these, students were also told to fill in a questionnaire. A qualitative analysis was carried out using the written accounts and interviews. Quantitative data collected, based on the survey questionnaire, served as useful supportive material. Findings from the analysis show that though many teenagers are aware of the lack of realism in Tamil movies, they do consume messages put forth by these movies in order to gratify various needs. However, the study indicates that what these teenagers obtain from the movies is largely determined by what they choose to obtain.